Binding site flexibility: Molecular simulation of partial and full agonists within a glutamate receptor - Arinaminpathy, Y; Sansom, M; Biggin, P (2006)
Ionotropic glutamate receptors mediate fast synaptic transmission in the mammalian central nervous system and play an important role in many different functions, including memory and learning. They have also been implicated in a variety of neuropathologies and as such have generated widespread interest in their structure and function. Molecular Dynamics simulations (5 x 20 ns) of the ligand-binding core of the GluR2 glutamate receptor were performed. Through simulations of both wild type and the L650T mutant, we show that the degree of protein flexibility can be correlated with the extent to which the binding cleft is open. In agreement with recent experiments, the simulations of kainate with the wild-type construct show a slight increase in β-sheet content that we are able to localize to two specific regions. During one simulation, the protein made a transition from an open-cleft conformation to a closed-cleft conformation. This closed cleft conformation closely resembles the closed-cleft crystal structure, thus indicating a potential pathway for conformational change associated with receptor activation. Analysis of the binding pocket suggests that partial agonists possess a greater degree of flexibility within the pocket that may help to explain why they are less efficient at opening the channel than full agonists. Examination of water molecules surrounding the ligands reveals that mobility in distinct subsites can be a discriminator between full and partial agonism and will be an important consideration in the design of drugs against these receptors. Copyright © 2006 The American Society for Pharmacology and Experimental Therapeutics.